An Overview of the Antibacterial Implications of Lansium domesticum - Tabassum Munir,; Khurrum Shahzad Munawar ,; Ayesha Mohyuddin, (Journal of Basic & Applied Sciences, 2018)
Lansium domesticum belongs to the family Meliaceae and is admired for its fruit in southern Asia. The family Meliaceae is known as novel bioactive compounds that are usually used in folk remedy as a drug for the treatment of diarrhea. The leaf and bark mixture of L. domesticum cv. duku exhibited antibacterial activity towards Bacillus subtile, Staphylococcus aureus, and Echerichia coli. Phytochemical screening of fruit waste of L. domesticum showed the presence of 3β -hydroxyonocera-8, 21α -hydroxyonocera-8, 14-dien-21-one and 14-dien-3-one, lansic acid. The seeds contain tetranortriterpenoids. The bark contains active compounds namely onoceradienedione, lansiolic acid A, iso-onoceratriene and 3-keto lansiolic acid. The methanolic extract of the bark of L. domesticum cv kokossan showed major antibacterial efficacy against Escherichia coli and. Bacillus subtilis The ethyl acetate extract exhibited an antibacterial efficacy with an inhibit zone respectively of 14 and 12.5 mm towards E. coli and B. cereus. Silver nanoparticles have a future in an antimicrobial role. The silver nanoparticles of L. domesticum are spherical in shape with a size from10-30 nm.